Contemporary challenges and prospects for sukuk - Ahmed, Essiea Ries; Islam , Md. Aminul; Ariffin , Ku Halim; Md., Moniruzzaman (Addleton Academic Publishers, 2013)
Islamic Sukuk (Islamic Bonds) has recently emerged as one of the most important tools for Islamic investment and finance. Sukuks are influencial and have effective impacts on various economic and banking transactions to the extent that they have secured a strong foothold in the international money and stock markets. Today Islamic Sukuk is one of the most successful financial products in the Islamic financial industry and one of the fastest growing sectors in the global financial landscape. This research identifies the contemporary challenegs that Islamic finance has been facing. It contends that Sukuk faces challenges on three fronts: sukuk as a market, development of sukuk and sukuk mechanisms.